Traditional Chinese medicine for COVID-19 pandemic and emerging challenges: An online cross-sectional survey in China - Chun-Li Lu; Ruo-Xiang Zheng; Xue Xue; Xiao-Wen Zhang; Xue-Han Liu; Xin-Yan Jin; Feng-Lan Pu; Hui-Di Lan; Min Fang; Ling-Yao Kong; Merlin Willcox; Bertrand Graz; et al. (Integrative Medicine Research)
Background: We aimed to investigate use of infection control behaviours, preventative and therapeutic interventions, and outcomes among respondents to an online survey during the COVID-19 pandemic in China. Methods: The survey was designed by an international team, translated and adapted to simplified Chinese, including 132 kinds of traditional Chinese medicine (TCM) preparation recommended by guidelines. It was distributed and collected from February to May 2021, with data analysed by WPS spreadsheet and wjx.cn. Descriptive statistics were used to describe demographics and clinical characteristics, diagnosis, treatments, preventative behaviours and interventions, and their associated outcomes. Results: The survey was accessed 503 times with 341 (67.8%) completions covering 23 provinces and four municipalities in China. Most (282/341, 82.7%) respondents reported no symptoms during the pandemic and the majority (290/341, 85.0%) reported having a SARS-CoV-2 PCR test at some point. Forty-five (13.2%) reported having a respiratory infection, among which 19 (42.2%) took one or more categories of modern medicine, e.g. painkillers, antibiotics; 16 (35.6%) used TCM interventions(s); while seven respondents combined TCM with modern medicine. All respondents reported using at least one behavioural or medical approach to prevention, with 22.3% taking TCM and 5.3% taking modern medicines. No respondents reported having a critical condition related to COVID-19. Conclusion: We found evidence of widespread use of infection control behaviours, modern medicines and TCM for treatment and prevention of COVID-19 and other respiratory symptoms. Larger scale studies are warranted, including a more representative sample exploring TCM preparations recommended in clinical guidelines.